Effect of charging ratio on thermal performance of a miniaturized two-phase super-heat-spreader. (January 2017) - Lv, Lucang; Li, Ji
Highlights: The effects of charging ratio on a miniaturized flat heat pipe were investigated. A temperature inverse increase along the heat pipe was observed. The flat heat pipe is insensitive to the gravity force. The heat pipe heat spreader has an infinite effective thermal conductivity at optimal charging ratio. Abstract: The effects of charging ratio on the thermal performance of a thin novel flat heat pipe (FHP) heat spreader under natural air convection were investigated systematically. Temperature difference and temperature distribution along the central axis of the flat heat pipe were measured carefully. Results show that there exists an optimal charging range for the FHP and a very small temperature difference was achieved, demonstrating superior heat spreading capability. Furthermore, a temperature inverse increase was observed in the condensation section. In addition, within the range of optimal charging ratios the flat heat pipe was insensitive to the gravity force. All the results indicate this novel type of two-phase heat spreader is very suitable for mobile electronics cooling in view of its high-performance as well as its easy processing.